The wisdom of Narnia - Lewis, C. S. (Clive Staples), 1898-1963.; Baynes, Pauline (New York : HarperCollins, 2001)
A collection of excerpts from the books in Lewis's "The Chronicles of Narnia" series.
Keywords: Lewis, C. S. -- 1898-1963 -- Quotations -- Juvenile literature; Narnia (Imaginary place) -- Juvenile literature; Lewis, C. S. -- 1898-1963 -- Quotations; Narnia (Imaginary place)